Acute Flaccid Paralysis: The New, The Old, and The Preventable. (9th December 2015) - Macesic, N.; Hall, V.; Mahony, A.; Hueston, L.; Ng, G.; Macdonell, R.; Hughes, A.; Fitt, G.; Grayson, M. L.
Abstract: Acute flaccid paralysis (AFP) has a changing epidemiology with ongoing polio outbreaks and emerging causes such as nonpolio enteroviruses and West Nile virus (WNV). We report a case of AFP from the Horn of Africa that was initially classified as probable polio but subsequently found to be due to WNV.